2014
DOI: 10.1002/etc.2698
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of endocrine disruption in zebrafish (Danio rerio) after discontinued exposure to the androgen 17β‐trenbolone

Abstract: The aim of the present study was to investigate the effects of the androgenic endocrine disruptor 17β-trenbolone on the sexual development of zebrafish (Danio rerio) with special emphasis on the question of whether adverse outcomes of developmental exposure are reversible or persistent. An exposure scenario including a recovery phase was chosen to assess the potential reversibility of androgenic effects. Zebrafish were exposed to environmentally relevant concentrations of 17β-trenbolone (1 ng/L-30 ng/L) from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 68 publications
(108 reference statements)
0
18
1
Order By: Relevance
“…Mixtures of organochlorine pesticides, polychlorinated biphenyls and brominated flame retardants have been shown to cause advanced puberty, measured as advanced timing of first spawning (Nourizadeh-Lillabadi et al, 2009). Most previous studies have investigated effects of EDCs on maturation only at the gonadal level (Baumann et al, 2013;Baumann et al, 2014;Kiparissis et al, 2003;Lin and Janz, 2006;Morthorst et al, 2010;Orn et al, 2006;Örn et al, 2003). The present study is the first to investigate effects on maturation as the timing of the physiological process of puberty, at both the pituitary and gonadal level of the HPG axis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Mixtures of organochlorine pesticides, polychlorinated biphenyls and brominated flame retardants have been shown to cause advanced puberty, measured as advanced timing of first spawning (Nourizadeh-Lillabadi et al, 2009). Most previous studies have investigated effects of EDCs on maturation only at the gonadal level (Baumann et al, 2013;Baumann et al, 2014;Kiparissis et al, 2003;Lin and Janz, 2006;Morthorst et al, 2010;Orn et al, 2006;Örn et al, 2003). The present study is the first to investigate effects on maturation as the timing of the physiological process of puberty, at both the pituitary and gonadal level of the HPG axis.…”
Section: Discussionmentioning
confidence: 69%
“…Sex differentiation in zebrafish occurs between about 20 and 35 days post fertilization (dpf) (Chen and Ge, 2012). It is well known that exposure to EDCs during sex differentiation can affect the sex ratio in fish with exposure to estrogens or antiandrogens causing female bias and exposure to androgens male bias (Antonopoulou et al, 1995;Baumann et al, 2014;Morthorst et al, 2010;Nimrod and Benson, 1998;Orn et al, 2006;Parrott and Blunt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Finch et al (2013) also found that 17␣-trenbolone (500 ng/L) resulted in decreases in body weight, snout-vent length, and total length of Xenopus laevis. Similarly, deceases in body weight and growth inhibition were observed in fish following exposure to high concentrations of 17␤-trenbolone (Baumann et al, 2014). The phenomenon that trenbolone promotes cattle growth but inhibits the growth of fish and tadpoles suggests that trenbolone might have an inhibitory effect on the growth of aquatic organisms rather than terrestrial vertebrates.…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have demonstrated that trenbolone can result in sex reversal, reproductive dysfunction, and even population decline in fish (Miller and Ankley, 2004;Orlando et al, 2004;Orn et al, 2006;Sone et al, 2005). Recently, researchers found that even a low dose (10-30 ng/L) of 17␤-trenbolone resulted in nearly 100% female-tomale sex-reversal in fish species (Baumann et al, 2014;Morthorst et al, 2010). Moreover, long-term exposure to 17␤-trenbolone was shown to inhibit fish growth (Baumann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation